Surface Reconstruction of Halide Perovskites During Post-treatment - YAVUZ, İLHAN (AMER CHEMICAL SOC, 2021)
Postfabrication surface treatment strategies have been instrumental to the stability and performance improvements of halide perovskite photovoltaics in recent years. However, a consensus understanding of the complex reconstruction processes occurring at the surface is still lacking. Here, we combined complementary surface-sensitive and depth-resolved techniques to investigate the mechanistic reconstruction of the perovskite surface at the microscale level. We observed a reconstruction toward a more PbI2-rich top surface induced by the commonly used solvent isopropyl alcohol (IPA). We discuss several implications of this reconstruction on the surface thermodynamics and energetics. Particularly, our observations suggest that IPA assists in the adsorption process of organic ammonium salts to the surface to enhance their defect passivation effects.
Keywords: SOLAR-CELLS; PERFORMANCE; EFFICIENCY